PENGEMBANGAN MODEL INDUKTIF KATA BERGAMBAR PADA PEMBELAJARAN MENULIS PERMULAAN DI KELAS II SD - Rachmawati Patty (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2015)
Abstract: The current study was intended to develop a set of picture word inductive model for vocabulary writing. The development processes included define, design, and develop. The subjects of the study were the second graders of the Inpres (presidential order) Elementary School 26 Batumerah. The data was collected by using observation, questionnaire, and achievement test. The results of the study were in the form of teaching and learning set including teaching and learning plans, students’ book, and students’ worksheet which could fulfill the criteria of valid, effective, and receiving positive response from the teachers. Abstrak: Penelitian ini bertujuan untuk mengembangkan perangkat model induktif kata bergambar (Picture Word Inductive Model) pada materi menulis kosa kata. Proses pengembangan ditempuh melalui define, design, dan develop. Subjek penelitian adalah siswa kelas 2 SD Inpres 26 Batumerah. Data dikumpulkan melalui observasi, angket, dan tes hasil belajar. Hasil penelitian berupa perangkat pembelajaran, meliputi rencana pelaksanaan pembelajaran, buku siswa, dan lembar kerja siswa yang memenuhi kriteria valid, efektif, dan respon positif dari guru.